Evaluasi dan Prediksi Pengelolaan Jaringan Air Bersih IKK Brangsong Kabupaten Kendal Berbasis Sistem Informasi Geografis dalam Rangka Mendukung Millenium Development Goals (MDGs) - Atmojo, Pranoto Samto; Sangkawati, Sri (Department of Civil Engineering, Diponegoro University, 2009)
To support government program Millennium Development Goals ( MDGS) where’s in the year 2015 : 80% of residents must be able to served by supply of cleanness water systems, hence writer will do evaluate of management and distribution of network supporting facilities for cleanness water based on technology that is using GIS ( Geographical Information System). GIS can stored technical data of cleanness water network, and GIS in allying with hydraulic model of EPANET applicable to evaluate network existing and assists to predict possibility future expansion of network ( eg the year 2015). This evaluation covers mapping of STA pipe network with GPS, mapping of continuation with GIS, calculation of scenario prediction clean water required in the year 2015, and handling of network supporting facilities for clean water with simulation EPANET for network existing and extension of either in the year 2008 and also for the year 2015. This research be done based on the real field condition there are: Cleanness water supplies for public IKK Brangsong supported by 2 pumping well. Its Part of Sub-Province Kendal area - that PDAM’s customer- no supplied by network especially at the peak hour time, and resent still have much region which has not been served clean water by PDAM ,so that’s need to extension network to supplied that area. Keywords: GPS, GIS, EPANETPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3417[How to cite: Atmojo, S.A. dan Sangkawati, S. (2009). Evaluasi dan Prediksi Pengelolaan Jaringan Air Bersih IKK Brangsong Kabupaten Kendal Berbasis Sistem Informasi Geografis dalam Rangka Mendukung Millenium Development Goals (MDGs), Jurnal Media Komunikasi Teknik Sipil, 17 (1): 98-109]